Drivers of productivity on the Agulhas Bank and the importance for marine ecosystems. (May 2022) - Jacobs, Zoe; Roberts, Mike; Jebri, Fatma; Srokosz, Meric; Kelly, Stephen; Sauer, Warwick; Bruggeman, Jorn; Popova, Ekaterina
Abstract: The Agulhas Bank, an area of broad continental shelf extending 250 km offshore of South Africa, sustains rich and productive fisheries. However, its primary production is driven by a complex mosaic of biophysical mechanisms, highly variable in time and space. The key drivers include a system of multiple costal upwellings, complex shelf currents and an interaction with the powerful Agulhas current. The patterns of spatial and temporal variability of primary production on the Agulhas Bank are critical for the spawning and survival of early life stages of many commercially important species exploited along the coastline of South Africa. In particular, the 'chokka' squid fishery is an important source of revenue for the Eastern Cape coastal region in South Africa, with low catch years causing socioeconomic hardship. After spawning on the Eastern Agulhas Bank, the squid paralarvae are thought to be transported west to the Central Agulhas Bank (CAB). This region is associated with a cool, productive, but rather intermittent, oceanic feature known as the 'cold ridge' (CR). If and when it occurs, this feature could provide a sufficient amount of concentrated (relative to the background values) food for the paralarvae to survive during its passive or near-passive stage. To date, a long-term analysis of CR variability and the mechanisms associated with this has not been conducted. Here, we used a high-resolution biogeochemical ocean model (NEMO-MEDUSA) to investigate the drivers of the productivity on the Agulhas Bank, specifically in the vicinity of the CR. Evidence of the CR is found from November to April and variability in its strength and spatial extent is comparable to that observed in remote sensing data. Interannual variability in productivity on the CAB is correlated to wind stress and zonal currents with the most productive events associated with anomalous easterly winds and enhanced westward flow on the Bank. These events coincide with the existence of an intense CR, important for overall productivity on the Bank, which may impact the recruitment of chokka squid and other fish species. From this simulation, we observe a season of low productivity in 2012 which may potentially relate to the infamous low catch in 2013 which caused economic hardship in the area.